Profitability-Based Financial Performance of PT Indoritel Makmur Internasional Tbk (2019–2023) - Putri Celine Tiofany; Siswanto Siswanto; Siti Junaidah Hasibuan (INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: This research aims to evaluate the financial performance of PT. Indoritel Makmur Internasional Tbk during the 2019-2023 period using profitability ratios, specifically Return on Assets (ROA) and Return on Equity (ROE), to determine the company's efficiency in asset utilization and equity management. Materials and methods: This qualitative research utilized secondary data from audited financial statements obtained from the Indonesia Stock Exchange (IDX) database. Financial performance was analyzed using descriptive-comparative methods, calculating ROA and ROE ratios and comparing results against industry standards (30% for ROA, 40% for ROE). Results: ROA fluctuated from 2.64% (2019) to a peak of 7.31% (2022), declining to 3.60% (2023), with a five-year average of 4.29%. ROE demonstrated similar patterns, ranging from 4.29% (2019) to 10.70% (2022), ending at 5.71% (2023), with an average of 6.73%. Both metrics remained consistently below industry benchmarks throughout the study period. Conclusions: PT. Indoritel Makmur Internasional Tbk's financial performance during 2019-2023 was classified as suboptimal based on profitability ratios. Despite positive growth trends in certain years, the company's inability to meet industry standards indicates inefficient asset and equity utilization, necessitating strategic interventions in operational efficiency, cost management, and revenue optimization.